Optimized Agronomic Management in North China Plain to Maintain Wheat (Triticum aestivum L.) Yield While Reducing Water and Fertilizer Inputs - Jiayu Ma; Chong Shang; Xuecheng Zhang; Baozhong Yin; Wenchao Zhen (Agronomy)
Optimizing farmers’ crop production management is an effective strategy to synergize yields, resource utilization, and environmental conservation. However, the mechanisms by which agronomic management in the North China Plain (NCP) determines the wheat yield, water use efficiency (WUE), and physiological performance remain largely unexplored. To address this knowledge gap, a field experiment was conducted from 2022 to 2024 to investigate the effects of conventional farmer practices (CK) and a Integrated High-Yield and Efficiency Cultivation Management (HHL) strategy incorporating pre-sowing soil moisture creation, optimized tillage, fertilization, and irrigation on the yield, water consumption characteristics, leaf photosynthetic physiology, and root traits. The results demonstrated that HHL significantly enhanced the root morphology in winter wheat compared to CK. Specifically, HHL increased the net photosynthetic rate (Pn), chlorophyll content, and leaf area index (LAI) at the flowering stage by 20.5%, 8.8%, and 11.1%, respectively, thereby boosting dry matter accumulation by 40.3% and yields by 10.9%. Furthermore, HHL reduced soil water evaporation by 12.1% and the total water consumption by 112.1 mm, while improving the WUE by 25.4% and nitrogen fertilizer partial productivity by 38.7%, alongside a 12.5% increase in economic benefits. Through rigorous field experimentation, this study elucidates the potential of HHL in water conservation, yield enhancement, and comprehensive benefit improvement, offering an effective cultivation paradigm for the wheat production systems in the NCP. The findings indicate that this management strategy exhibits superior water-saving and yield-enhancing effects, with promising prospects for widespread adoption and application.